Pengaruh Good Corporate Governance Terhadap Kinerja Keuangan Dan Nilai Perusahaan: Studi kasus pada Perusahaan Badan Usaha Milik Negara (BUMN) periode 2018 s.d 2020 - Nurhidayanti, Fenny; Listari, Sinta; Efrianti, Desi (Institut Bisnis dan Informatika Kesatuan, 2023)
There is an awareness that companies that apply the principles of good corporate governance can improve financial performance and company value. The implementation of good corporate governance can help improve transparency, accountability, and company compliance with applicable regulations. This can help reduce the risk of company failure and increase investor confidence. This study aims to examine the effect of good corporate governance as measured by the size of the board of directors, independent board of commissioners, and the size of the audit committee on financial performance and company value in state-owned companies for the period 2018 to 2020. The purposive sampling method was used to select 20 companies as research samples with a total data sample of 60 data for 3 years. The results showed that the size of the board of directors had a significant positive effect on financial performance and a significant negative influence on company value, while the independent board of commissioners had a significant negative effect on financial performance and a significant positive influence on company value. The size of the audit committee has no effect on the financial performance and value of the company. Financial performance also affects the value of the company positively and significantly. From the results of the study, it can be concluded that the implementation of Good Corporate Governance, especially on the size of the board of directors and independent board of commissioners, affects financial performance and company value. This study provides strong empirical evidence on the importance of implementing Good Corporate Governance in improving corporate performance and value. However, further research is still needed to evaluate other factors that can affect company performance and value. Keywords : Good Corporate Covernance, Board of Directors Size, Independent Board of Commissioners, Audit Committee Size, Return On Asset (ROA), Price to Book Value Ratio (PBV).